Shell microstructures (disturbance lines) of Arctica islandica (Bivalvia): a potential proxy for severe oxygen depletion - Höche, Nils; Zettler, Michael L.; Huang, Xizhi; Schöne, Bernd R. (Frontiers in Marine Science, 2023)
The spread of oxygen deficiency in nearshore coastal habitats endangers benthic communities. To better understand the mechanisms leading to oxygen depletion and eventually hypoxia, predict the future development of affected ecosystems, and define suitable mitigation strategies requires detailed knowledge of the dissolved oxygen (DO) history. Suitable high-resolution DO archives covering coherent time intervals of decades to centuries include bivalve shells. Here, we explored if the microstructure, specifically disturbance lines, in shells of Arctica islandica from the Baltic Sea can be used as an alternative or complementary proxy to Mn/Cashell to track the frequency and severity of past low-DO events. Disturbance lines differ from periodic annual growth lines by the presence of fine complex crossed lamellae instead of irregular simple prisms. Aside from a qualitative assessment of microstructural changes, the morphology of individual biomineral units (BMUs) was quantitatively determined by artificial intelligence-assisted image analysis to derive models for DO reconstruction. As demonstrated, Mn-rich disturbance lines can provide a proxy for past deoxygenation events (i.e., DO < 45 µmol/L), but it currently remains unresolved if low DO leads to microstructurally distinct features that differ from those caused by other environmental stressors. At least in studied specimens from the Baltic Sea and Iceland, low temperature, salinity near the lower physiological tolerance, or food scarcity did not result in disturbance lines. With decreasing DO supply, disturbance lines seem to become more prominent, contain more Mn, and consist of increasingly smaller and more elongated BMUs with a larger perimeter-to-area ratio. Although the relationship between DO and BMU size or elongation was statistically significant, the explained variability (<1.5%) was too small and the error too large to reconstruct DO values. BMU parameters may reveal a closer relationship with DO if studied in three dimensions and if the DO content was determined at high resolution, directly at the position where the bivalves lived, something that future work should address.